Human Cytomegalovirus Persistently Infects Aortic Endothelial Cells - Fish, Kenneth N. (American Society for Microbiology, 1998)
Endothelial cells (EC) have been implicated as constituting an important cell type in the pathogenesis of human cytomegalovirus (HCMV). Microvascular and macrovascular EC exhibit different biochemical and functional properties depending on the organ of origin. Phenotypic differences between microvascular and macrovascular EC may alter the ability of these cells to support HCMV replication. In this study, we compared the replication of HCMV in primary macrovascular aortic EC (AEC) with that in brain microvascular EC (BMVEC). An examination of IE72, pp65, and gB viral antigen expression in BMVEC and AEC by immunoflourescence revealed similar frequencies of infected cells. Intracellular production of virus was 3 log units greater in BMVEC than in AEC, while equal quantities of extracellular virus were produced in both cell types. HCMV infection of BMVEC resulted in rapid cellular lysis, while the virus was nonlytic and continuously released from HCMV-infected AEC for the life span of the culture. An examination of infected cells by electron microscopy revealed the formation of abundant nucleocapsids in both AEC and BMVEC. However, significant amounts of mature viral particles were only detected in the cytoplasm of BMVEC. These observations indicate that levels of HCMV replication in EC obtained from different organs are distinct and suggest that persistently infected AEC may serve as a reservoir of virus.